The efficacy and tolerance of high pressure oxygen combined with chemotherapy in postoperative patients with advanced gastric cancer - Qian, Changlin; Liu, Hua; Zhang, Jie; Shen, Zhiyong (Translational Cancer Research, 2018)
Background: The aim of this study was to investigate the clinical efficacy analysis and tolerance observation of hyperbaric oxygen combined with chemotherapy in postoperative patients with advanced gastric cancer. Methods: A total of 56 patients from June 2014 to June 2015 with advanced gastric cancer postoperative chemotherapy were collected. These patients were randomly divided into the experimental group of 22 patients treated with hyperbaric oxygen combined with chemotherapy, and the control group of 23 patients treated with conventional chemotherapy. The results of imaging evaluation, tumor index, adverse reaction of chemotherapy and quality of life (QOL) were compared between the two groups. Results: The recurrence rate of 1 year imaging was 4.54% and 26.0% respectively in the experimental group and the control group, and the two groups had statistical differences (P=0.046); The persistent abnormal index of CA199, showed in the experimental group and the control group, accounting for 13.6% and 43.4% severally, which showed statistical differences (P=0.027); Compared with the control group, the incidence of hemocytopenia, thrombocytopenia, nausea and vomiting and peripheral nervous reaction were reduced in the experimental group, and there was a statistically significant difference between the two groups (P